(untitled) (Physical Education, Health and Social Sciences, 2025)
The first case was identified in December 2019, the Human coronavirus disease 2019 (HCOV-19), caused by the severe acute respiratory syndrome coronavirus 2, spread quickly, resulting in a global pandemic. As of early 2025, the virus infected over 200 countries, with over 3.5 million cases and an estimated 165,000 to 243,000 fatalities. Largely characterized by respiratory and cardiovascular complications, recent studies highlight the wide-ranging effect of the virus on the nervous system. The neurological presentations range from mild manifestations, such as headache (in about 10–20% of patients), dizziness, and hyposmia—the most frequent peripheral nervous system symptom—to severe complications, such as encephalopathy, acute cerebrovascular disease (e.g., ischemic stroke and intracerebral hemorrhage), Guillain-Barré syndrome, and sporadic cases of acute transverse myelitis or encephalitis. Importantly, neurological deficits may occur prior to the onset of characteristic respiratory symptoms (such as fever and cough) in 20–30% of cases, making early diagnosis challenging and allowing for transmission risks in the healthcare setting. Pathophysiologic mechanisms remain to be explored but are likely to include direct viral neuroinvasion through angiotensin-converting enzyme 2 receptors, cytokine storm induction due to systemic inflammation, and hypercoagulability with subsequent thrombotic events. Delirium and encephalopathy are more common in critically ill patients and may be due to hypoxia or multiorgan failure. Chronic neurological sequelae like cognitive impairment and postexertional fatigue are increasingly observed in "long COVID" patients, and this suggests that monitoring in the long term may be necessary. This review consolidates current situation of the neurological spectrum of HCOV-19 and the need for early detection and multidisciplinary management. Frontline doctors and neurologists need to remain in increased suspicion of SARS-CoV-2 infection in patients with acute neurological syndromes, regardless of respiratory symptoms, to facilitate early isolation and treatment. Research is necessary to unravel the neurotropic capacity of the virus, maximize therapeutic intervention, and prevent long-term disability burden.